Adaptation of the diaphonization protocol and the highlight of some significant structures development in the chicken embryo (Gallus gallus) skeleton - Leonard CALISTRU; Alexandru Nicolae STERMIN (Studia Universitatis Babeș-Bolyai. Biologia)
Diaphonization is a technique used in developmental biology, anatomy, and comparative morphology to visualize and study the internal structures of small organisms. In this study, we used diaphonization to visualize the development of chicken embryos (Gallus gallus). Diaphonization was performed on chicken eggs at different stages of development, from 10 to 13 days of incubation, and the resulting specimens were analyzed using microscopy. The results suggest that for embryos older than 14 days, a longer storage time in 1% KOH is recommended (approximately 30% longer incubation time compared to the original protocol). In the case of more developed chicken embryos, it is also recommended to carry out evisceration. These results provide insight into the early stages of avian development and may have applications in the fields of developmental biology and anatomy.